Rheumatoid Arthritis Patients Have Better Outcomes Than Non-Rheumatoid Arthritis Patients When Hospitalized for Ischemic Stroke: Analysis of the National Inpatient Sample. Issue 1 (14th January 2022) - Edigin, Ehizogie; Ojemolon, Pius Ehiremen; Eseaton, Precious Obehi; Shaka, Hafeez; Akuna, Emmanuel; Asemota, Iriagbonse Rotimi; Manadan, Augustine
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: The aims of this study were to compare the outcomes of patients primarily admitted for ischemic stroke with and without a secondary diagnosis of RA. Methods: Data were abstracted from the National Inpatient Sample (NIS) 2016 and 2017 database. The NIS was searched for hospitalizations for adult patients with ischemic stroke as principal diagnosis with and without RA as secondary diagnosis using International Classification of Diseases, 10th Revision codes. The primary outcome was inpatient mortality. Hospital length of stay (LOS), total hospital charges, odds of receiving tissue plasminogen activator, and mechanical thrombectomy were secondary outcomes of interest. Multivariate logistic and linear regression analyses were used accordingly to adjust for confounders. Results: There were more than 71 million discharges included in the combined 2016 and 2017 NIS database. Of 525, 570 patients with ischemic stroke, 8670 (1.7%) had RA. Hospitalizations for ischemic stroke with RA had less inpatient mortality (4.7% vs. 5.5%; adjusted odds ratio, 0.66; 95% confidence interval, 0.52–0.85; p = 0.001), shorter LOS (5.1 vs 5.7 days, p < 0.0001), lower mean total hospital charges (61, 626 vs. 70, 345, p < 0.0001), and less odds of undergoing mechanical thrombectomy (3.9% vs. 5.1%; adjusted odds ratio, 0.55; 95% confidence interval, 0.42–0.72; p < 0.0001) compared with those without RA. Conclusions: Hospitalizations for ischemic stroke with RA had less inpatient mortality, shorter LOS, lower total hospital charges, and less likelihood of undergoing mechanical thrombectomy compared with those without RA. However, the odds of receiving tissue plasminogen activator were similar between both groups. Further studies to understand its mechanism would be helpful.